Seismic Hazard Assessment For Peninsular Malaysia Using Gumbel Distribution Method - Adnan, Azlan; Hendriyawan, Hendriyawan; Marto, Aminaton; Irsyam, Masyhur (Penerbit UTM Press, 2005)

(untitled)
This Paper Presents The Preliminary Study On Seismic Hazard Assessment Which Involved Developing Macrozonation Map For Two Hazard Levels, I.E. 10% And 2% Probabilities Of Exceedance In 50 Years For Bedrock Of Peninsular Malaysia. The Analysis Was Performed Using Statistic Theory Of Extreme Values From Gumbel. The Analysis Covered The Earthquake Data Processing (Such As Choosing A Consistent Magnitude To Be Used In The Analysis And Identifying Main Shock Events), And Selection Of Appropriate Attenuation Relationship. Results Showed That The Peak Ground Acceleration (PGA) Across The Peninsular Malaysia Range Between 10 And 25 Gal For 10% Probability Of Exceedance, And Between 15 And 35 Gal For 2% Probability Of Exceedance In 50 Years Hazard Levels. These Values Were Lower By About 50 To 65% Than Those Obtained From Deterministic Analysis.